Positive solutions to second order boundary value problems / Wan Ashraf Wan Azmi - Wan Azmi, Wan Ashraf (2014)
This thesis is concerned with the existence of positive solutions for second order boundary value problems. In particular, firstly we investigate the existence and multiplicity of positive solutions for a singular second order scalar Sturm-Liouville boundary value problem with different values of A for a function / involve u. Then, we investigate the existence of positive solutions of a Dirichlet boundary value problem where the function / involve u and v!. Lastly, we consider the results of positive solutions for singular Dirichlet second order boundary value problem where the function / involve u and vl in terms of different values of A. The existence results of positive solutions are proved by applying the Krasnosel'skii fixed point theorem on compression and expansion of cones.